Quercetin inhibits the cAMP/PKA/CREB/glycolysis axis to exert anti-acute lymphoblastic leukemia effects - Ma, Qiuling; Liu, Wenqing; Su, Yajing; Guo, Jue; Zhang, Man; Guo, Jiayuan; Liu, Mingxin; Dong, Wenbo; Li, Mingwei; Wang, Bo (Frontiers in Pharmacology, 2025)
Acute lymphoblastic leukemia (ALL), an aggressive hematologic malignancy with high incidence and treatment resistance, demands novel therapeutic approaches. Enhanced glycolysis is a hallmark of metabolic reprogramming in ALL. Quercetin (Que) demonstrates broad antitumor effects by inhibiting glycolysis and cell proliferation. Previous studies have shown that Que significantly suppresses the proliferation of ALL cells and induces apoptosis; however, its mechanistic basis remains elusive. In this study, we demonstrate that Que triggers mitochondrial dysfunction, activating the intrinsic apoptosis pathway and inducing G2/M phase cell cycle arrest. Que markedly reduces glucose uptake, lactate production, and ATP synthesis in ALL cells, suggesting a dual inhibitory effect on both oxidative phosphorylation (OXPHOS) and glycolysis. Mechanistically, Que inhibits the cAMP/PKA/CREB axis, substantially reducing both mRNA and protein levels of glycolytic enzymes (HK2, PFKP, and PKM2). Notably, the PKA-specific agonist Sp-cAMP (50 μmol/L) completely rescues Que-mediated effects. Collectively, Que’s dual pro-apoptotic and anti-proliferative actions through the cAMP/PKA/CREB/glycolysis axis establish a molecular foundation for Que-based ALL therapies.